Aspiration, Ethnic Composition, and Competitive Inclination - Li, King King,Shen, Peiyao (SSRN, 2022)
How does differences in the competitive inclination of ethnic groups contribute to economic disparity and how does the ethnic composition of a group affect competitive inclinations of individuals from different ethnicities? We experimentally investigate how ethnic composition affects the competitive inclinations of those from the Han (ethnic majority) and Yi (ethnic minority) in groups with different ethnic compositions. In homogeneous treatments, which consists of one ethnicity, we find no differences in competitive inclination. However, in mixed treatments where both ethnicities are present in the group, the Yi are less likely to enter tournament than the Han, supporting the hypothesis that ethnic composition affects tournament entry decisions. The difference in aspiration for education attainment of the Yi and the Han has the highest explanatory power for this entry-gap. Difference in income, performance, and parents' education cannot explain the entry-gap. The results suggest that the government's preferential university admission policy for ethnic minorities leads to the Yi having lower aspirations, which in turn leads to a lower entry rate in the mixed treatments
10.2139/ssrn.4127991
Keywords: Arbeitspapier; Graue Literatur; Competitive inclination; Ethnicity; Aspiration; Gender difference